2008
DOI: 10.1007/s11422-008-9151-8
|View full text |Cite
|
Sign up to set email alerts
|

Tough transitions? Mediating beginning urban teachers’ practices through coteaching

Abstract: The coteaching model for teacher preparation has emerged in recent years as an alternative to the traditional student teaching or practicum experience. Several studies have investigated the process of coteaching and its impact on participants during the actual experience; however, few depict participants' experiences once they obtain positions and begin to teach independently. This collective case study explored two urban high school teachers' (Jen and Ian) practices during the induction period after taking pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…Over the past two decades research on teachers and teaching has consistently reported that teaching is an emotionally, physically and intellectually demanding job (Hargreaves, 1994;Kyriacou, 2000;Troman and Woods, 2001;Wassell and LaVan, 2009;Zembylas and Schutz, 2009). Excessive working hours, pupils' disruptive behaviour and a lack of leadership support challenge teachers' capacity to maintain their enthusiasm and passion for teaching and are often found to be key contributing factors to teacher attrition and stress (Ingersoll, 2003;Robinson, 2003 andJohnson, 2004;Bryk et al, 2010;Day and Gu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades research on teachers and teaching has consistently reported that teaching is an emotionally, physically and intellectually demanding job (Hargreaves, 1994;Kyriacou, 2000;Troman and Woods, 2001;Wassell and LaVan, 2009;Zembylas and Schutz, 2009). Excessive working hours, pupils' disruptive behaviour and a lack of leadership support challenge teachers' capacity to maintain their enthusiasm and passion for teaching and are often found to be key contributing factors to teacher attrition and stress (Ingersoll, 2003;Robinson, 2003 andJohnson, 2004;Bryk et al, 2010;Day and Gu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The societal relations that characterize any transactional space also develop along with participants' development. In our study, the cogenerative dialogue meetings constituted such a space, because these presupposed the unique understandings and experiences of each participant (Wassel;Lavan, 2009). Consequently, it would be expected that all participants were enacting an equitable approach to making sense and generating and understanding of praxis (Roth;Zimmerman, 2002b).…”
Section: Toward a More Symmetrical Approach To The Zone Of Proximal Dmentioning
confidence: 96%
“…We discuss the literature for studies that have infused cogen and PAR and the changes that took place. Wassell and LaVan (2009) commented that cogen is an evolution of PAR. To begin with, both PAR and cogen studies involved social practices.…”
Section: Integrating Cogen In Parmentioning
confidence: 99%